Schools of social entrepreneurship: a triple theoretical proposal to focus your study (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
In academia there is still no consensus in defining the concept of social entrepreneurship, and there are various approaches and interpretations. Clarity in its definition to differentiate it from traditional entrepreneurship is necessary. The main objective of this paper was to develop a taxonomy of the concept of social entrepreneurship through a review of literature, describing three schools of thought, namely: (i) the school of social enterprise, (ii) the school of social entrepreneur and (iii) the school of social innovation.
Keywords: social entrepreneurship; social enterprise; social entrepreneur; social innovation; schools of thought